A Citrus Blackfly Parasitoid, Encarsia perplexa Huang & Polaszek (Insecta: Hymenoptera: Aphelinidae) - Ru Nguyen; Thomas R. Fasulo (EDIS)
Revised! EENY-242, a 3-page illustrated fact sheet by Ru Nguyen and T.R. Fasulo, is part of the Featured Creatures collection. It describes this effective parasitoid of citrus blackfly — distribution, description, life cycle, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, April 2010.